Cutaneous manifestations in COVID-19 patients in a district COVID care centre - Dasari, Prathyusha; Chowdary, Swetha A.; Samanthula, Haritha; Ruvva, Soumya (International Journal of Research in Dermatology, 2021)
Background: COVID-19, initially started as respiratory illness and evolved to involve various systems. Skin has been the least targeted organ with manifestations limited to case reports and series in a foreign scenario. Here, we tried to understand a same in an Indian scenario. Methods: This was cross-sectional study done in district COVID centre among patients with a confirmed diagnosis of COVID-19 with cutaneous manifestations for 3 months. A detailed history, complete cutaneous examination was carried out. Timing in relation to other symptoms and severity was assessed. Results: Among the 1603 patients, 39 (2.4%) had skin manifestations. Urticaria (20.5%), petechiae/purpura (17.9%), pruritis (15.4%) were the most common followed by maculo-papular rash (7.7%), manifestations secondary to drugs (7.7%), diffuse hair fall (7.7%), pseudo-chilblains (5.1%), vesicular eruptions (5.1%), infections (5.1%), cellulitis, gangrene and livedoid vasculitis. Timing of skin lesions ranged from 2 days before (10.3%) onset of COVID-19 symptoms or diagnosis to 10 days after (69.2%). Urticaria, petechiae, maculopapular rash were seen more commonly in patients with fever and respiratory symptoms. Asymptomatic cases showed urticaria, petechiae and pseudo-chilblains. Majority were in mild and moderate disease and livedoid vasculitis patient had severe disease. Conclusions: Skin manifestations in COVID-19 are relatively uncommon in Indian scenario. However, few of the manifestations give a hint of infection while some correlate with the severity of disease.